Strategi Toko Tradisional Kawan Kita dalam Meningkatkan Kualitas Layanan Penjualan: Perspektif Etika Bisnis Islam - Ummal Khoiriyah (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2019)
Kawan Kita traditional shop apply several strategies to improve service quality of sales by providing training, education, assessment and communication pattern in the Islamic business ethics perspective. This research is a qualitative research with a descriptive approach that aims to describe strategies in improving service quality and Islamic business ethics perspective. Based on the results of the research, the strategies in improving the service quality in the Islamic business ethics perspective applied in Kawan Kita traditional shop are: human resource management is run well, based on Qur'an and Hadith. Among them is by providing training on Islamic business ethics, evaluating employees, approaching employees directly (hablum minannas), and communicating well and correctly according to Islamic law.